2016
DOI: 10.1038/srep28010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of different CTC subpopulations in non-small cell lung cancer

Abstract: Circulating tumour cells (CTCs) serve as valuable biomarkers. However, EpCAM positive CTCs are less frequently detected in NSCLC patients compared to other epithelial tumours. First, EpCAM protein expression was analysed in primary and metastatic lung cancer tissue. In both groups 21% of the samples were EpCAM negative. Second, the CellSearch system identified 15% of patients (n = 48) as CTC positive whereas a multiplex RT-PCR for PIK3CA, AKT2, TWIST, and ALDH1 following EGFR, HER2 and EpCAM based enrichment d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 33 publications
3
95
2
Order By: Relevance
“…In principle, the concordance of genomic alterations between tumor biopsies and CTCs/ctDNA has been demonstrated by several reports, both for EGFR mutations (62)(63)(64) and ALK translocations (50,54,65), leading to the inclusion of CTCs/ ctDNA in clinical trials as prognostic/predictive biomarkers. The results of these studies suggest that monitoring EGFR mutations or EML4-ALK rearrangements in the circulating compartment can reveal therapy resistance also prior to radiological progression evidence, thus guiding the therapeutic decision in the patient clinical course (62,65) (32,68). Notably, these studies also indicate the mandatory need to use methods that are more sensitive in the analysis of tumor biopsies at diagnosis, rather than Sanger sequencing.…”
Section: Exploring the Metastatic Potential Of Lung Ctcsmentioning
confidence: 99%
See 3 more Smart Citations
“…In principle, the concordance of genomic alterations between tumor biopsies and CTCs/ctDNA has been demonstrated by several reports, both for EGFR mutations (62)(63)(64) and ALK translocations (50,54,65), leading to the inclusion of CTCs/ ctDNA in clinical trials as prognostic/predictive biomarkers. The results of these studies suggest that monitoring EGFR mutations or EML4-ALK rearrangements in the circulating compartment can reveal therapy resistance also prior to radiological progression evidence, thus guiding the therapeutic decision in the patient clinical course (62,65) (32,68). Notably, these studies also indicate the mandatory need to use methods that are more sensitive in the analysis of tumor biopsies at diagnosis, rather than Sanger sequencing.…”
Section: Exploring the Metastatic Potential Of Lung Ctcsmentioning
confidence: 99%
“…Several studies associate CTC number to OS and/or PFS of metastatic NSCLC patients (32,33,48,57), meanwhile others do not find these associations (70,71). Many small trials have also demonstrated the association between CTC count and therapy efficacy, comparing the count before and after therapy (38,(72)(73)(74), or during target therapy, in order to detect the onset of resistance mutations (50,54,62,66,75).…”
Section: The Long Road Towards Clinical Utilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Single-cell molecular analysis based on CTCs can be applied as a research tool to reveal the mechanisms of metastases and resistance to targeted therapy [75,76]. Additionally, CTCs could be useful for the following purposes: as noninvasive surrogates for HE staining to definitively diagnose NSCLCs, for FISH testing to guide ALK-targeted therapy and for mRT-PCR testing to detect the MET and HER3 gene amplifications that are related to the resistance to EGFR-TKI therapy, when suitable tissue biopsies are unavailable [77,78].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%